Is the “Gift of Life” a Resonant Frame? A Comparison of Factors Involved in Non-Directed Kidney Donor Motivation for Social Workers and Nurses - Humphries, PhD, Harry L.; Conrad, PhD, Browyn K.; Humphrey, PhD, Kristen R.; Giffin, BS, Kathryn A.; Giefer, PhD, APRN, Cheryl K.; Hite, DNP, APRN, Amy L. (The Journal of Nephrology Social Work, 2016)
This research examines kidney donor motivations using a research design from prior investigations evaluating the persuasiveness of the National Kidney Foundation’s (NKF) altruistic “gift of life” frame. Because previous studies produced mixed results, showing in particular substantially more support for material incentives among an international sample of nursing professionals, as compared to a convenience sample of college students, we compared in this study the motivations among practitioners in the fields of nursing and social work. A total of 159 social workers and nurses participated in a survey that addressed the relationship between material incentives, social distance and motivation to donate, as well as work-related burnout and compassion fatigue as structural factors that might reduce non-directed kidney donor motivation. The results show a significant negative relationship between altruism and donor motivation, as measured by social distance between donor and recipient, and a strong lack of support for direct cash incentives as a complement to living kidney donation. The results also show little support for the notion that compassion fatigue or burnout accounts for these results. Social workers are somewhat more altruistic than nurse practitioners but the differences between the two groups are not meaningful. However, low support for living donations to unrelated others, coupled with high support for limited material incentives for both groups, suggest a continued need to explore alternatives to the current framing of kidney donations as giving the “gift of life.”